Royce'un Hayatı ve Felsefi Eserleri - Önder, Bilgin (Ankara Üniversitesi, 2008)
Royce’s Life and Works. Josiah Royce is an important philosopher to serve as a sourcefor, above all, historians of philosophy, researchers of philosophy of religion, social psychology,sociology of religion, philosophy of politics, medical ethics, philosophy of education and ethics.Since it is aimed in this article to introduce Royce, one of the original thinkers of American Philosophyin many respects, to the Turkish scientific and intellectual circles readers, various aspects of hislife, works, intellectual career and his philosophy have been drawn attention